Aktivitas Penghambatan Trichoderma spp. Formulasi terhadap Jamur Patogen Tular Tanah secara In vitro - S. M. Widyastuti; Sumardi Sumardi; Irfa'i Irfa'i; H. H. Nurjanto (Universitas Gadjah Mada, 2002)
The research was aimed to evaluate the growth of formulated conidia propagules of Trichoderma koningii, T. reesei and T. harzianum, which had been stored for 1 and 5 months and the inhibition activity against soil borne plant pathogenic fungi Rigidopous lignosus, Ganoderma sp., Fusarium sp., and Sclerotium rolfsii. The isolates were formulated in the forms of alginate bead, alginate-peat bead, and peat-lime powder. The results indicated that Trichoderma formulated stored at room temperature showed higher inhibition activity than that stored at 4oC. After 5 months in the storage, T. reesei in both bead and powder formula performed higher growth inhibition activity against soil borne pathogens than the other isolates tested. It was noted that all isolates performed temporary decreased growth inhibition activity against soil borne pathogens.